2014
DOI: 10.1159/000358837
|View full text |Cite
|
Sign up to set email alerts
|

MRI Predicts Remission at 1 Year in First-Episode Schizophrenia in Females with Larger Striato-Thalamic Volumes

Abstract: Background/Aims: The Remission in Schizophrenia Working Group has defined remission as ‘a low-mild symptom intensity level, maintained for a minimum of 6 months, where such symptoms do not affect an individual's behaviour' [Andreasen et al.: Am J Psychiatry 2005;162:441-449]. Since brain morphology relates to symptomatology, treatment and illness progression, MRI may assist in predicting remission. Methods: Thirty-nine patients newly diagnosed with DSM-IV schizophrenia underwent MRI brain scan prior to antipsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Finally, we systematically reviewed clinical studies within the past five years to predict the outcome of patients with schizophrenia and/or other psychotic disorders (Supporting information Table S4) using MRI, widely including high‐resolution T1‐weighted imaging (Altamura et al, ; Dusi et al, ; Francis et al, ; Fung et al, ; Hutcheson et al, ; Molina et al, ; Morch‐Johnsen et al, ; Palaniyappan et al, ; Premkumar et al, ), BOLD‐fMRI (Hadley et al, ; Kraguljac, White, Hadley, Visscher et al, ; Kraguljac, White, Hadley, Hadley et al, ; Li, Jing et al, ; Nejad et al, ; Sarpal et al, ), diffusion tensor imaging (Crossley et al, ; Reis Marques et al, ), and arterial spin labeling (Stegmayer et al, ). In spite of relatively low predictive capacity (72.7%‐82.1% sensitivity and 62.5%‐68.6% specificity) compared with tests previously discovered (80% sensitivity and 75% specificity) (Sarpal et al, ), we propose this novel tool for early prediction as an alternative approach to contribute to the current potential markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we systematically reviewed clinical studies within the past five years to predict the outcome of patients with schizophrenia and/or other psychotic disorders (Supporting information Table S4) using MRI, widely including high‐resolution T1‐weighted imaging (Altamura et al, ; Dusi et al, ; Francis et al, ; Fung et al, ; Hutcheson et al, ; Molina et al, ; Morch‐Johnsen et al, ; Palaniyappan et al, ; Premkumar et al, ), BOLD‐fMRI (Hadley et al, ; Kraguljac, White, Hadley, Visscher et al, ; Kraguljac, White, Hadley, Hadley et al, ; Li, Jing et al, ; Nejad et al, ; Sarpal et al, ), diffusion tensor imaging (Crossley et al, ; Reis Marques et al, ), and arterial spin labeling (Stegmayer et al, ). In spite of relatively low predictive capacity (72.7%‐82.1% sensitivity and 62.5%‐68.6% specificity) compared with tests previously discovered (80% sensitivity and 75% specificity) (Sarpal et al, ), we propose this novel tool for early prediction as an alternative approach to contribute to the current potential markers.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, a relatively high level of regional activity might reflect its sensitivity to treatment in patients with schizophrenia. Furthermore, according to the structural and functional neuroimaging results, in a volumetric MRI study (Huang et al, 2015), a group of schizophrenia patients exhibit reduced gray matter volume in contrast to healthy (Altamura et al, 2017;Dusi et al, 2017;Francis et al, 2018;Fung et al, 2014;Hutcheson et al, 2014;Molina et al, 2014;Morch-Johnsen et al, 2015;Palaniyappan et al, 2013;Premkumar et al, 2015), BOLD-fMRI (Hadley et al, 2014;Kraguljac, White, Hadley, Visscher et al, 2016;Li, Jing et al, 2017;Nejad et al, 2013;Sarpal et al, 2016), diffusion tensor imaging (Crossley et al, 2017;Reis Marques et al, 2014), and arterial spin labeling (Stegmayer et al, 2017). In spite of relatively low predictive capacity (72.7%-82.1% sensitivity and 62.5%-68.6% specificity) compared with tests previously discovered (80% sensitivity and 75% specificity) (Sarpal et al, 2016), we propose this novel tool for early prediction as an alternative approach to contribute to the current potential markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, response to therapy for depression has been associated with baseline resting state network activity (75) and regional white matter integrity (72). Response to antipsychotic therapy has been associated with decreased white matter integrity and volume reduction in several regions (76)(77)(78)(79)(80)(81)(82). Response to cognitive behavioral therapy in PTSD has been associated with anterior cingulate activity and volume, as well as amygdala activity (83,84).…”
Section: The Challenges Of Overdiagnosismentioning
confidence: 99%
“…Biomarkers based on data derived from brain imaging have recently shown considerable promise in estimating individual clinical outcome. 3 , 4 Magnetic resonance imaging (MRI) studies have found neuroanatomical differences such as structural morphology, 5 volume, 6 , 7 ventricle size, 8 and cortical thickness, 9 , 10 as well as differences in functional connectivity 11–13 to be associated with likelihood of AP response.…”
Section: Introductionmentioning
confidence: 99%